Convergent synthesis of stereoisomers of THF ring moiety of acetogenin thiophene analogue and their antiproliferative activities against human cancer cell lines. Issue 17 (27th April 2017) - Matsumoto, Takuya; Kojima, Naoto; Akatsuka, Akinobu; Yamori, Takao; Dan, Shingo; Iwasaki, Hiroki; Yamashita, Masayuki
Abstract: The convergent synthesis of thiophene-3-carboxamide analogues of annonaceous acetogenins was accomplished through the asymmetric alkynylation of a 2-formyl THF ring fragment with an alkyne having a thiophene ring as the key step. Eight stereoisomers of the THF ring moiety were synthesized by this convergent route and their antiproliferative activities against 39 human cancer cell lines were evaluated. It was revealed that derivatives having the threo configuration between C17–C18 positions showed more potent activities than the corresponding erythro ones. Graphical abstract: